Energy and exergy analyses of a transcritical CO2 air conditioning system for an electric bus. (25th May 2021) - Song, Xia; Lu, Daxiong; Lei, Qiang; Wang, Dandong; Yu, Binbin; Shi, Junye; Chen, Jiangping
Highlights: A CO2 air conditioning system was developed for use in an electric bus. The system achieved a good cooling performance in a hot climate. The effect of the working conditions on the cooling performance were investigated. Exergy analysis of the system at various working conditions was performed. Significant irreversibility occurred in the gas cooler and the expansion process. Abstract: The cooling performance of a transcritical CO2 air conditioning system for an electric bus was investigated using energy and exergy analyses. The effects of the working conditions, such as the compressor speed, electronic expansion valve (EEV) opening, inlet temperature and flow rate of indoor air and the inlet temperature of outdoor air on the energy performance were experimentally investigated. Exergy analysis of the system was performed based on the experimental data. Experimental results showed a coefficient of performance (COP) of 2.88 and a cooling capacity of 31.4 kW at a condition of 35 °C/27 °C (an outdoor air temperature of 35 °C and an indoor air temperature of 27 °C). As the outdoor air temperature increased to 45 °C, a COP of 1.87 was achieved with a cooling capacity of 22.8 kW. Therefore, the system possessed a good cooling performance in hot climates. Increasing the indoor air flow rate could improve the exergy efficiency of the system and increasing the indoor and outdoor air temperatures could reduce the exergy efficiency of the system. Among the exergy destructions of the components, the values obtained for the gas cooler and EEV accounted for significant proportions, offering great opportunities for improving the system performance. In extremely hot climates the exergy destruction of EEV comprised the greatest percentage and further research should be performed on the significant throttling loss of the expansion process.